INDUCED REPRODUCTION OF BLACK-FINNED PACU Colossoma macropomum USING PITUITARY EXTRACTS FROM COMMON CARP AND PIRARUCU - RODRÍGUEZ CHU, Luciano Alfredo (2022)
Hypophysation was the first known induced reproduction technique in fish farming and, it continues being applied to this day. The study aimed to evaluate the reproductive response of adult males and females of black-finned pacu Colossoma macropomum, induced with injections of paiche pituitary extract (EPP) and carp pituitary extract (CPE). We used ten females and ten males with an average body weight of 6,81 ± 1,86 kg and 6,59 ± 2,34 kg, respectively. Four females were treated with carp pituitary extract (CPE) at 6,0 mg/kg body weight, while another six received paiche pituitary extract (PPE) at 3,5 mg/kg body weight. In both cases, the dose was administered in two injections (10% at the beginning and 90% twelve hours later). Four males were induced with EPC and six with EPP at 1 mg/kg body weight administered in two 50% doses simultaneously as the females. The females induced with the EPP spawned in their entirety, while with the EPC only 75% of them. The means of total weight of spawned oocytes, number of oocytes per gram, absolute fecundity, hatching rate and the total number of larvae produced from the two hormonal treatments used in the present study did not present significant differences (P>0.05). The present work demonstrated that it is possible to carry out the induced reproduction of Colossoma macropomum using paiche pituitary extract.